The untold truancy stories: a case study in Malaysia - Tai, Soo Shong; Abu Bakar Ah, Siti Hajar (The Malaysian Journal of Social Administration, 2017)
Abstract This collective qualitative case study explored the truancy experiences of six habitual truants between the ages of 13-17 who reside in an Approved School in Kuala Lumpur. The purpose of this study was to examine the kind of activities that these habitual truants used to participate so as to gain a deeper insight into their lifestyle, behavioural patterns, and living habits as well as the seriousness of truancy. The researcher used the purposive sampling strategy in the selection of the six participants. The data generation methods used in this study include interviews, observations, and document analysis. The findings that emerged from this study showed that these habitual truants used to skip classes, sneak out of the school, stay out late, and look for ways to make money during school hours, take drugs, steal, rob, break into shops or houses, and waste their time hanging around looking for mischief. All these antisocial activities eventually caused them to end up as school failures and landed them in the juvenile school. Keywords: truancy, antisocial behaviour, mischief, theft, loafing, prevention.